2007
DOI: 10.1007/s00464-007-9457-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of types of resection and manipulation on trocar site contamination after laparoscopic colectomy: An experimental study in rats with intraluminal radiotracer application

Abstract: Background The etiology and incidence of port-site metastases after laparoscopic surgery for colorectal cancer remain unknown. The purpose of this experimental study was to detect and quantify the amount of contamination at the port-site by means of a method utilizing radiolabelled colloid particles following extra-or intracorporeal laporoscopic resection of cecum. Methods Prior to experimental surgery, we obtained a high concentration of luminal colonic radiotracer activity by per anum application of sulphur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Only in the study by Polat et al . was it identified that an entire laparoscopic caecum resection was performed using two endoloops [23]. Additionally, most studies do not list all operation parameters in detail (such as the way stumps are disinfected, the kinds of trocar or incision that were used and to what extent they enlarged the incision to exteriorize the resectate) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only in the study by Polat et al . was it identified that an entire laparoscopic caecum resection was performed using two endoloops [23]. Additionally, most studies do not list all operation parameters in detail (such as the way stumps are disinfected, the kinds of trocar or incision that were used and to what extent they enlarged the incision to exteriorize the resectate) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While most investigators used barbiturate [19,20,22] or ketamine [16-18,21,23] for narcosis, we used isoflurane (Forene®, Abbott GmbH & Co KG, Wiesbaden, Germany), which was also used by Schmelzer et al . [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations